Satisfaction of the Dental Service Users at Some Clinical Externships, Faculty of Dentistry, University of Costa Rica - Gutiérrez-Marín, Natalia (2023)
The objective of this research was to determine the degree of satisfaction of dental service users in some clinical externships at the Faculty of Dentistry from the University of Costa Rica during the year 2022, through the application of a modification of the Dental Satisfaction Questionnaire. The sample population consisted of 396 patients and/or legal guardians who attended during May and June of this year at the “Rotación Clínica Comunitaria Palmares,” “Rotación Sede del Atlántico (Turrialba-Guápiles),” “Rotación en Externado Clínico Recinto Paraíso”, “Rotación Clínica del Externado de San Ramón” and “Rotación Comunitaria del curso externado clínico en la Clínica Dental del Recinto de Grecia.”  An instrument was applied, physically or digitally, which included DSQ questions and sociodemographic data. Descriptive analysis of all variables was performed. To establish whether there was an association between sociodemographic variables and DSQ, the Kolmogorov-Smirnov tests, Mann-Whitney U test, Kruskal-Wallis test and the post-hoc Bonferroni test were implemented. The response rate was 49.32%; participants indicated satisfaction with the dental service. There was a statistically significant difference not only between the variable of sex and availability, but also between the domains (satisfaction, access, pain management, availability and quality) and the different externships. The study population is satisfied with the dental service received; however, there are significant differences in the DSQ domains and each externship.